Politics of risk taking. Welfare state reform in advanced democracies - Vis, Barbara (Amsterdam, 2010)
"How much and in which direction have the welfare states among the Western democracies changed over the past decades? Moreover, under which conditions have governments enacted these changes? Based on insights from prospect theory, a psychological theory of choice under risk, Vis demonstrates ably that the context in which governments find themselves (losses or gains) affects their attitude towards risk and thereby the degree and type of reform they pursue. Facing socio-economic losses or political ones, governments accept the electoral risk involved in unpopular reforms, such as benefit cutbacks; confronting gains, they steer away from them. The study's new theoretical stance and innovative methodological approach (fuzzy-set analysis) make Politics of Risk-Taking a must read for policymakers, scholars as well as students interested in the politics of welfare state reform."